2017
DOI: 10.3390/molecules22030502
|View full text |Cite
|
Sign up to set email alerts
|

Carapanosins A–C from Seeds of Andiroba (Carapa guianensis, Meliaceae) and Their Effects on LPS-Activated NO Production

Abstract: Two new phragmalin-type limonoids, Carapanosins A and B (1 and 2), and a new gedunin-type limonoid, Carapansin C (3), together with five known limonoids (4–8) were isolated from the oil of Carapa guianensis AUBLET (Meliaceae) seeds, a traditional medicine in Brazil and Latin American countries. Their structures were elucidated on the basis of spectroscopic analyses using 1D and 2D NMR techniques and HRFABMS. Compounds 1–8 were evaluated for their effects on the production of NO in LPS-activated mouse peritonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Andiroba oil is already described with great healing potential. Researches that oil effectively participates in wound healing by promoting the formation of granulation, tissue contraction and epithelialization (Burlando & Cornara, 2017;Higuchi et al, 2017). According to Souza et al (2017) compared to the control group or andiroba oil showed surprising results, obtaining a lower average of the wound area compared to the control group, mainly macroscopically with a degree of almost total contraction of the incisional wound.…”
Section: Healing Activitymentioning
confidence: 99%
“…Andiroba oil is already described with great healing potential. Researches that oil effectively participates in wound healing by promoting the formation of granulation, tissue contraction and epithelialization (Burlando & Cornara, 2017;Higuchi et al, 2017). According to Souza et al (2017) compared to the control group or andiroba oil showed surprising results, obtaining a lower average of the wound area compared to the control group, mainly macroscopically with a degree of almost total contraction of the incisional wound.…”
Section: Healing Activitymentioning
confidence: 99%
“…An inhibitory assay of nitric oxide production was performed according to a method reported previously [14] with slight modifications. Briefly, RAW264.…”
Section: Inhibitory Assay Of No Productionmentioning
confidence: 99%
“…Our series of studies on the components of the seed oil of C. guianensis revealed the structures of carapanolides A and B [ 8 ], guianolide A and B [ 9 ], carapanolides C–I [ 10 ], carapanolides J–L [ 11 ], carapanolides M–S [ 12 ], carapanolides T–X [ 13 ], and carapanosins A–C [ 14 ] in the seed oil of andiroba. Last year, we reported the absolute structure of guianolactones A and B from the seed oil of C. guianasis (Meliaceae) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%